Mathematical Model of COVID-19 with Aspects of Community Compliance to Health Protocols - Gautama, I Putu Winada; Wijayakusuma, IGN Lanang; Swastika, Putu Veri; Dwipayana, I Made Eka (Jurnal Matematika UNAND, 2025)
COVID-19 infection is still a health problem in various countries. Some people who recover from COVID-19 still experience some symptoms. Therefore, it is essential to implement health protocols to minimize transmission of the COVID-19 virus. Based on this, a mathematical model of COVID-19 with aspects of community compliance with health protocols is presented. The population is divided into three subpopulations: the susceptible subpopulation, the exposed subpopulation, and the infected subpopulation. The basic reproduction number, $R_0$, determines whether there are disease-free and endemic equilibrium points. When $R_0$ is less than 1, the disease-free equilibrium is locally asymptotically stable. Conversely, when $R_0$ is greater than 1, the endemic equilibrium point is locally stable. Numerical simulations will demonstrate how COVID-19 spreads, taking into account community adherence to health guidelines. The results of numerical simulations indicate that an increase in public adherence to health protocols leads to a decrease in the number of COVID-19 infections.